2012
DOI: 10.1371/journal.ppat.1002796
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biodiversity Changes in Disease Risk: Exploring Disease Emergence in a Plant-Virus System

Abstract: The effect of biodiversity on the ability of parasites to infect their host and cause disease (i.e. disease risk) is a major question in pathology, which is central to understand the emergence of infectious diseases, and to develop strategies for their management. Two hypotheses, which can be considered as extremes of a continuum, relate biodiversity to disease risk: One states that biodiversity is positively correlated with disease risk (Amplification Effect), and the second predicts a negative correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
91
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 50 publications
6
91
0
7
Order By: Relevance
“…Although an increasing number of studies have reported negative correlations between host diversity and disease risk (29,38,39), the hidden effects of concurrent changes in parasite communities have rarely been explored (19,31,40). Future studies examining the biodiversity-disease relationship should focus more heavily on the relative importance of multiple components of biodiversity (and how they covary) in driving observed patterns in disease risk (41)(42)(43), including the direct and indirect effects of hosts, nonhosts (e.g., predators and competitors), parasites, as well as other microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although an increasing number of studies have reported negative correlations between host diversity and disease risk (29,38,39), the hidden effects of concurrent changes in parasite communities have rarely been explored (19,31,40). Future studies examining the biodiversity-disease relationship should focus more heavily on the relative importance of multiple components of biodiversity (and how they covary) in driving observed patterns in disease risk (41)(42)(43), including the direct and indirect effects of hosts, nonhosts (e.g., predators and competitors), parasites, as well as other microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported (Pagán et al . ) that higher levels of human management of chiltepin are associated with higher prevalence of plants showing symptoms of viral infection. A large fraction of symptomatic plants were infected by begomoviruses, specifically by Pepper golden mosaic (PepGMV) and Pepper huasteco yellow vein virus (PHYVV).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular ecology research shows that the genomic sequence of viruses acquire signatures which describe their histories that help in understanding the ecological patterns and evolutionary processes. These patterns can be understood if natural host range is known (Traore et al, 2009 (Pagan et al, 2012). A bright future of plant virus ecology is ahead because the combination of molecular and traditional approaches in the discipline are being brought together to collect the details of virus genetic variations and epidemic breakouts which were impossible in the previous years (Jones, 2014a).…”
Section: Molecular Ecologymentioning
confidence: 99%